Microstructural Evolution and Mechanical Performance of Two Joints of Medium-Mn Stainless Steel with Low- and High-Alloyed Steels - Khedr, Mahmoud; Ibrahim, I. Reda; Jaskari, Matias; Ali, Mohammed; Abdel-Aleem, Hamed A.; Mahmoud, Tamer S.; Hamada, Atef (Materials, 2023)
In this work, 2 mm thick medium-Mn austenitic stainless steel (MMn–SS) plates were joined with austenitic NiCr stainless steel (NiCr–SS) and low-carbon steel (LCS) using the gas tungsten arc welding technique. A precise adjustment of the welding process parameters was conducted to achieve high-quality dissimilar joints of MMn–SS with NiCr–SS and LCS. The microstructural evolution was studied using laser scanning confocal and electron microscopes. Secondary electron imaging and electron backscatter diffraction (EBSD) techniques were intensively employed to analyze the fine features of the weld structures. The mechanical properties of the joints were evaluated by uniaxial tensile tests and micro-indentation hardness (HIT). The microstructure of the fusion zone (FZ) in the MMn–SS joints exhibited an austenitic matrix with a small fraction of δ-ferrite, ~6%. The tensile strength (TS) of the MMn–SS/NiCr–SS joint is significantly higher than that of the MMn–SS/LCS joint. For instance, the TSs of MMn–SS joints with NiCr–SS and LCS are 610 and 340 MPa, respectively. The tensile properties of MMn–SS/LCS joints are similar to those of BM LCS, since the deformation behavior and shape of the tensile flow curve for that joint are comparable with the flow curve of LCS. The HIT measurements show that the MMn–SS/NiCr–SS joint is significantly stronger than the MMn–SS/LCS joint since the HIT values are 2.18 and 1.85 GPa, respectively.